1980
DOI: 10.1136/hrt.44.4.464
|View full text |Cite
|
Sign up to set email alerts
|

Rupture of pulmonary artery aneurysm associated with persistent ductus arteriosus.

Abstract: SUMMARY Fatal haemopericardium occurred in a 14-year-old boy after rupture of a pulmonary artery aneurysm. Persistent ductus arteriosus with severe pulmonary hypertension was confirmed by cardiac catheterisation when he was 4 weeks old. Attempted closure of the ductus at 4 years had not been possible because of apparent high pulmonary resistance. Exercise tolerance had been good enough to permit competitive horse riding up to the day ofdeath. Light and electron microscopy showed widespread cystic medionecrosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

1983
1983
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 4 publications
0
8
0
1
Order By: Relevance
“…Histologic examinations of such patients have also shown that cystic medial necrosis was a prominent feature. 3,4 In our patient, there was a continuous murmur on physical examination. Two-dimensional echocardiography revealed continuous left-to-right shunt from aorta to PA, with a significant pressure gradient (maximum Doppler measured velocity of the ductal jet in systole was 5 m/s), which indicates that there was no significant pulmonary arterial hypertension.…”
Section: Discussionmentioning
confidence: 90%
“…Histologic examinations of such patients have also shown that cystic medial necrosis was a prominent feature. 3,4 In our patient, there was a continuous murmur on physical examination. Two-dimensional echocardiography revealed continuous left-to-right shunt from aorta to PA, with a significant pressure gradient (maximum Doppler measured velocity of the ductal jet in systole was 5 m/s), which indicates that there was no significant pulmonary arterial hypertension.…”
Section: Discussionmentioning
confidence: 90%
“…In most cases of patent ductus arteriosus, the flow of blood from the aorta to the pulmonary artery ranges from 2 to 10 L/min, resulting in a total pulmonary blood flow of 6 to 15 L/min [9]. Although mild dilatation of the pulmonary artery is often observed in cases of patent ductus arteriosus, true aneurysm occurs in only 15% of cases, and may be due to the combined effects of pulmonary hypertension and other contributing factors, such as atheromatous disease, endocarditis, and tuberculosis [12].…”
Section: Discussionmentioning
confidence: 98%
“…In this patient, the cause of death was rupture of the wall of a pulmonary artery aneurysm, which demonstrated severe cystic medial necrosis and elastin fragmentation attributable to the pulmonary hypertension (4)(5)(6)(7). The most interesting finding in this case was the arteriosclerosis involving the descending thoracic and abdominal aortas.…”
Section: Discussionmentioning
confidence: 99%